Ambassador Message Ja’far Bin Abi Thalib In The Wayang Kekayon Khalifah - Lutfianto; Abdul Munip (Proceeding International Conference on Religion, Science and Education, 2023)
This paper aims to discuss the model for the creation of Wayang Kekayon Khalifah characters. This figure is a means of conveying the message of the ambassador of the Prophet Muhammad's friend who asked for asylum in the land of Habasyah, namely Ja'far bin Abi Talib. Wayang Kekayon Khalifah is a new wayang model. This creation uses the Artistic Research method and a Practice Based Research thinking scheme, focusing on contemporary works of art. The purpose of this creation is to develop practice-based science. Next how to realize the cowhide. So the message of the Islamic ambassador through the existing decorations and ornaments uses an aesthetic approach and leather craft. The design of this leather craft work will produce artifacts in the form of wayang gunungan paraga Ja'far bin Abi Talib, which is part of the wayang Kekayon Khalifah with ornaments and decorations and calligraphy of the names of the characters.